Infliximab as rescue therapy in hospitalised patients with steroid‐refractory acute ulcerative colitis: a long‐term follow‐up of 211 Swedish patients. Issue 4 (25th June 2013) - Sjöberg, M.; Magnuson, A.; Björk, J.; Benoni, C.; Almer, S.; Friis‐Liby, I.; Hertervig, E.; Olsson, M.; Karlén, P.; Eriksson, A.; Midhagen, G.; Carlson, M.; et al.
Summary: Background: Rescue therapy with infliximab (IFX) has been proven effective in a steroid‐refractory attack of ulcerative colitis (UC). The long‐term efficacy is not well described. Aim: To present a retrospective study of IFX as rescue therapy in UC. Primary end points were colectomy‐free survival at 3 and 12 months. Methods: In this multicentre study, 211 adult patients hospitalised between 1999 and 2010 received IFX 5 mg/kg as rescue therapy due to a steroid‐refractory, moderate‐to‐severe attack of UC. Exclusion criteria were duration of current flare for >12 weeks, corticosteroid treatment for >8 weeks before hospitalisation, previous IFX therapy or Crohn's disease. Results: Probability of colectomy‐free survival at 3 months was 0.71 (95% CI, 0.64–0.77), at 12 months 0.64 (95% CI, 0.57–0.70), at 3 years 0.59 (95% CI, 0.52–0.66) and at 5 years 0.53 (95% CI, 0.44–0.61). Steroid‐free, clinical remission was achieved in 105/211 (50%) and 112/209 (54%) patients at 3 and 12 months respectively. Of 75 colectomies during the first year, 48 (64%) were carried out during the first 14 days, 13 (17%) on days 15–90 and 14 (19%) between 3 and 12 months. There were three (1.4%) deaths during the first 3 months. Conclusions: Infliximab is an effective rescue treatment, both short‐ and long‐term, in a steroid‐refractory attack of UC. Most IFX failures underwent surgery during the first 14 days, which calls for studies on how to optimise induction treatment with IFX. Serious complications, including mortality, were rare.